Alchohol Consumption Practices in the Koryak Community - Lyudmila N. Khakhovskaya (Journal of Ethnology and Folkloristics)
The article is dedicated to the analysis of alcohol consumption practices within the Koryak ethno-cultural community. The aim of the article is to understand how the reasons for alcohol consumption are explained within the framework of the community. The analysis is based on the ideas of Durkheim’s social theory. The author of the article claims that the practice of consuming alcohol is essentially connected with the more archaic practice of mushroom consumption since both have a grounding in the Koryak perception of the world. The analysed models of behaviour stem from appropriate Koryak epistemology and ontology, which themselves are based on the notion of the ‘other world’ and communication with supernatural entities (spirits). The isomorphism of consuming alcohol and amanita intoxication reflects the inner core of this connection: the Koryak believe that an entity enters the human body and controls their actions. The transition from one type of intoxication to another is accompanied by drastic transformation of the materiality of the consumed product, which, in turn, leads towards social transformations. Such social changes are qualified as anomie by the author of the article. The visual materiality of the amanita mushroom dictated its symbolic anthropomorphism and creation of special rules for the treatment (amanita codex). The physical amorphousness of vodka does not imply the same intellectual work. The author claims that this factor was one of the reasons why the Koryak do not have social regulations about vodka consumption – which leads to mass alcoholism. It is possible that indigenous communities have difficulties in working out the required social regulations because of the complexities surrounding the non-utilitarian treatment of the unusual materiality of vodka.